Ernest W. Peterkin papers - Peterkin, Ernest W.
Correspondence, journal, writings, notebook, orders, photoreproduction of sketchbook, and other papers kept by Peterkin as a member of the scientific group which photographed the atomic blasts during Operation Crossroads, the nuclear testing on Bikini Atoll, Marshall Islands, in 1946.
Library of Congress Prints and Photographs Division.
Naval officer and engineer. Born 1920; died 1995.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Nuclear weapons -- Testing; Operation Crossroads, Marshall Islands, 1946.; Bikini Atoll (Marshall Islands) -- History; Engineers; Naval officers